(untitled) (Baghdad Science Journal, 2004)
Anew Solar concentrator have been designed in this paper, this concentrators Were based on the total internal reflection in a prism, the prism angles has been calculated by depending on the solar incident ray angle in baghdad for a year. The optical design consist ofa triangular presume, Where the solar cells on one side of the prism Wh?le the prism head towered the south. The results show that there is an increasing in the solar ray concentrators and the cell area is reduced.